Internalisasi Nilai Karakter Melalui Pembiasaan Jumat BERSERI (Bersih, Sehat, Literasi, dan Istighosah) di Madrasah Ibtidaiyah - Muhammad Syahrul Muharram; Istianatul Milah; Choirul Anwar; Faris Nur Haq (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study investigates the internalization of character values through the BERSERI (Clean, Healthy, Literacy, and Istighosah) Friday Habbit at Madrasah Ibtidaiyah as a school culture–based model of character education. The study aims to explain how routine religious, literacy, and health practices contribute to students’ character formation. A qualitative descriptive design was applied at MI Hidayatun Najah Tuban. Data were collected through participatory observation, in-depth interviews with teachers and school leaders, and document analysis. Data credibility was ensured through triangulation, and inductive thematic analysis was employed to interpret the findings. Results show that the BERSERI Friday Habit effectively integrates character education into daily school life. Clean and healthy activities develop discipline, responsibility, and environmental awareness; literacy sessions strengthen critical thinking and learning motivation; and istighosah enhances spiritual awareness, emotional stability, and moral conduct. The program also fosters a supportive school culture marked by collective responsibility, religious atmosphere, and positive social interaction. Overall, the BERSERI program offers a practical model for sustainable character internalization in Islamic primary education.